Reputations, relationships and the enforcement of incomplete contracts - W. Bentley MacLeod (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper discusses the literature on the enforcement of incomplete contracts. It compares legal enforcement to enforcement via relationships and reputations. A number of mechanisms, such as the repeat purchase mechanism (Klein and Leffler (1981)) and efficiency wages (Shapiro and Stiglitz (1984)), have been offered as solutions to the problem of enforcing an incomplete contract. It is shown that the efficiency of these solutions is very sensitive to the characteristics of the good or service exchanged. In general, neither the repeat purchase mechanism nor efficiency wages is the most efficient in the set of possible relational contracts. In many situations, total output may be increased through the use of performance pay and through increasing the quality of law.
Keywords: D86; K12; C7; O17; 330; Unvollständiger Vertrag; Vertragstheorie; Prestige; Rechtsdurchsetzung; Theorie